Study of aged central auditory function using the auditory middle latency response - De Oliveira, Anna Caroline Silva [UNESP]; Alcântara, Yara Bagali [UNESP]; De Góes, Viviane Borim [UNESP]; Menezes, Pedro de Lemos; Chagas, Eduardo Federighi Baisi; Machado, Milena Sonsini [UNESP]; Frizzo, Ana Claudia Figueiredo [UNESP] (My University, 2023)
Objective: Investigate the auditory function of the elderly using the middle latency potentials. Methodology: Group 1 (G1): 20 healthy individuals of both genders, older than 60 years, without hearing loss. Group 2 (G2): 20 healthy individuals of both sexes, older than 60 years, with hearing loss in frequencies from 4 to 8 kHz. Potential recording was performed with unilateral and bilateral stimulation and the Binaural Interaction Component was calculated. Results: Na latency in C3A1 was greater in the stimulation of the right ear in G2 and the amplitude of Na-Pa was greater in the stimulation of the right ear and recording in C3A1 in G1. The latency of the Pa component was higher in the stimulation of the right ear recorded in C4A2. The Pb component in G2 by bilateral stimulation and recorded in C4A2 had higher latency. The first and second negative and positive peaks presented greater amplitude in G1. In C3A1, the 1st negative peak was more negative in G1 and the 2nd positive peak showed greater amplitude in C4A2 in both groups. Conclusion: The transmission of auditory information to the primary auditory cortex is impaired with aging, especially in unilateral stimulation, reinforced by losses in elderly people with peripheral hearing loss, such as in the binaural interaction at the cortical and subcortical levels. Thus, the AMLR has shown to be a sensitive examination to investigate neuroauditory disorders in the elderly, especially related to high-frequency hearing loss and primary auditory cortex dysfunctions caused by the aging process.
Keywords: Acoustic stimulation; Aged; Auditory cortex; Auditory evoked potentials